Cdc13 at a crossroads of telomerase action - GELI, Vincent; churikov, Dmitri; Luciano, Pierre; Corda, Yves (Frontiers in Oncology, 2013)
Telomere elongation by telomerase involves sequential steps that must be highly coordinated to ensure the maintenance of telomeres at a proper length. Telomerase is delivered to telomere ends, where it engages single-strand DNA end as a primer, elongates it, and dissociates from the telomeres via mechanism that is likely coupled to the synthesis of the complementary C-strand. In Saccharomyces cerevisiae, the telomeric G-overhang bound Cdc13 acts as a platform for the recruitment of several factors that orchestrate timely transitions between these steps. In this review, we focus on some unresolved aspects of telomerase recruitment and on the mechanisms that regulate telomere elongation by telomerase after its recruitment to chromosome ends. We also highlight the key regulatory modifications of Cdc13 that promote transitions between the steps of telomere elongation.